Dose‐efficient multimodal microscopy of human tissue at a hard X‐ray nanoprobe beamline. (16th March 2022) - Sala, Simone; Zhang, Yuhe; De La Rosa, Nathaly; Dreier, Till; Kahnt, Maik; Langer, Max; Dahlin, Lars B.; Bech, Martin; Villanueva-Perez, Pablo; Kalbfleisch, Sebastian
Abstract : This work presents the implementation of combined high‐resolution X‐ray in‐line holography and X‐ray fluorescence microscopy within the same experimental setup at a hard X‐ray nanofocusing beamline. In‐line holography provides morphological information by recovering electron density maps, even on weakly scattering or low‐contrast samples; X‐ray fluorescence provides complementary chemical information by producing element‐specific mass density maps. Abstract : X‐ray fluorescence microscopy performed at nanofocusing synchrotron beamlines produces quantitative elemental distribution maps at unprecedented resolution (down to a few tens of nanometres), at the expense of relatively long measuring times and high absorbed doses. In this work, a method was implemented in which fast low‐dose in‐line holography was used to produce quantitative electron density maps at the mesoscale prior to nanoscale X‐ray fluorescence acquisition. These maps ensure more efficient fluorescence scans and the reduction of the total absorbed dose, often relevant for radiation‐sensitive ( e.g. biological) samples. This multimodal microscopy approach was demonstrated on human sural nerve tissue. The two imaging modes provide complementary information at a comparable resolution, ultimately limited by the focal spot size. The experimental setup presented allows the user to swap between them in a flexible and reproducible fashion, as well as to easily adapt the scanning parameters during an experiment to fine‐tune resolution and field of view.